Interrogating rapid design ethnography : a strategy for exploring the indigenous visual vernaculars of the Ghanaian Adinkra symbols - Reyburn, Duncan (University of Pretoria, 2016)
Mini Dissertation (MA)--University of Pretoria, 2016.